Preparation method of corrosion and scale inhibitor
By modifying the chemical bonding and molecular chain entanglement of polyaspartic acid and hydrolyzed polymaleic anhydride, combining imidazoline oleoyl polyamine type corrosion inhibitor and nanomaterial, a scale inhibitor with significant corrosion inhibition and scale inhibition effect under high temperature conditions was prepared, which solved the problem of poor temperature resistance of existing scale inhibitors.
Patent Information
- Application Number
- CN202510134258.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-02-07
AI Technical Summary
The existing scale inhibitors have poor temperature resistance under high temperature conditions, making it difficult to effectively prevent scale formation, affecting the normal operation of petrochemical equipment.
A method of preparing corrosion inhibitor is adopted to enhance scale resistance by chemical bonding and molecular chain winding of modified polyaspartic acid and hydrolyzed polymaleic anhydride to form a dense protective film, and imidazoline oleoyl polyamine corrosion inhibitor, 2-amino-5-methyl-4-phenylthiazole, nanotitanium dioxide, nanozinc oxide and other components are added to enhance scale resistance.
In high temperature environments, the corrosion inhibition and scale inhibition effects are significantly improved, effectively preventing corrosion and scale formation of metal equipment, extending equipment life and reducing maintenance costs.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of scale inhibitors, and more specifically, to a method for preparing a corrosion and scale inhibitor. Background Art
[0002] With the global exploitation of crude oil, the reserves of high-quality light crude oil are gradually decreasing, and the newly exploited crude oil often contains more heavy components. In particular, the crude oil produced in some emerging oil producing areas has a large density and high viscosity, and the asphaltene and colloid content is relatively high. At the same time, in order to pursue a higher yield of light oil products, the operating conditions of the unit are becoming increasingly harsh, and the processing depth is increasing, resulting in the heavy raw materials used in the processing processes such as hydrocracking, catalytic diesel and coking diesel. Impurities in the raw materials, such as metal impurities, sulfur and nitrogen compounds, and macromolecular substances (such as asphaltene, colloid, etc.), are prone to cause scaling and other problems during the processing process, which seriously affects the normal operation of the unit, reduces production efficiency, and increases equipment maintenance costs and energy consumption.
[0003] In order to solve this problem, scale inhibitors are used as an effective chemical method. Scale inhibitors will not change the existing process flow, will not affect normal operation, and are easy and flexible to add. However, in some processes of petrochemical industry, such as hydrocracking and coking diesel, the temperatures involved are relatively high, but the existing scale inhibitors have poor temperature resistance and are difficult to meet the actual working conditions, resulting in frequent scaling, which seriously affects production efficiency and equipment life.
[0004] The patent application document with publication number CN114591760A discloses a scale inhibitor used in the oil refining process, which is composed of component A, component B, component C, component D and a solvent, wherein component A is a nitrogen oxide free radical-N-heterocyclic compound; component B is di(2-ethylhexyl) phosphate, component C is ethylenediamine polyoxyethylene polyoxypropylene ether; component D is N,N′-di-sec-butyl-p-phenylenediamine, and the rest is a solvent; the mass ratio of component A: component B: component C: component D is 5:14:12:20, and the rest is a solvent.
[0005] In the patent application document, the component B used contains phosphorus, which may enter the water body with wastewater after use, causing eutrophication of the water body and posing a potential threat to the environment; component C has poor temperature resistance. In the refining process, it may be unable to withstand high temperatures and cause molecular chain breakage or structural changes, thereby losing its proper anti-scaling properties such as dispersion and emulsification. Summary of the invention
[0006] In view of the problems of existing scale inhibitors, a scale inhibitor that does not contain phosphorus and is temperature-resistant should be developed. To this end, the present application provides a method for preparing a corrosion inhibitor.
[0007] The present application provides a method for preparing a corrosion and scale inhibitor, which adopts the following technical solution: A method for preparing a corrosion and scale inhibitor comprises the following steps: S1: dissolving 25-35 parts by mass of modified polyaspartic acid in hydrogenated diesel, adding an antioxidant, and mixing well to obtain solution A; S2: dissolving 15-25 parts by weight of hydrolyzed polymaleic anhydride in hydrogenated diesel and mixing well to obtain solution B; S3: 6-10 parts by weight of imidazoline oleyl polyamine corrosion inhibitor and 1-2 parts by weight of 2-amino-5-methyl-4-phenylthiazole are uniformly mixed to obtain a mixture C; S4: adding 0.4-0.7 parts by mass of sodium dodecylbenzene sulfonate to hydrogenated diesel, mixing evenly, and then adding nano titanium dioxide and nano zinc oxide in a mass ratio of 1-2:1, mixing evenly, to obtain a dispersion D; S5: dissolving 4 to 8 parts by weight of the dispersant in hydrogenated diesel and mixing them uniformly to obtain a solution E; S6: Under an inert atmosphere, solution A and solution B are mixed in a reactor, mixed evenly, heated to react, then mixture C is added, mixed evenly, heated to react, cooled, solution E is added, mixed evenly, then dispersion D is added, mixed evenly, heated to react, cooled, solid-liquid separation is performed, and distillation is performed to obtain a corrosion and scale inhibitor; The total amount of the nano titanium dioxide and nano zinc oxide is 4 to 7 parts by weight.
[0008] Preferably, in step S6, under an inert atmosphere, solution A and solution B are mixed in a reactor, mixed evenly, heated to 110-130°C, reacted for 1.5-2.5 hours, mixture C is added, mixed evenly, heated to 150-170°C, reacted for 4-6 hours, cooled to 90-110°C, solution E is added, mixed evenly, then dispersion D is added, mixed evenly, heated to 130-150°C, reacted for 3-5 hours, cooled, solid-liquid separation is performed, and distillation is performed to obtain a corrosion inhibitor and scale inhibitor.
[0009] Preferably, the dispersant is polyisobutylene succinimide.
[0010] Preferably, the antioxidant is antioxidant 1010, and the amount of the antioxidant 1010 is 0.5% to 1% of the mass of the modified polyaspartic acid.
[0011] Beneficial effects: First, after solution A and solution B are mixed, on the one hand, the molecular chains of modified polyaspartic acid and hydrolyzed polymaleic anhydride are interconnected and entangled, and the protective film formed on the metal surface is more compact, which can more effectively prevent corrosive substances (such as sulfides, acidic substances, etc.) from contacting the metal. The corrosion inhibition mechanisms of the two complement each other. Modified polyaspartic acid mainly inhibits corrosion by chelating metal ions, while hydrolyzed polymaleic anhydride can slow down corrosion by adsorbing on the metal surface to change its surface properties. This synergistic effect makes the corrosion inhibition effect more significant. At the same time, the chelation of modified polyaspartic acid can effectively capture scale-forming metal ions (such as calcium ions and magnesium ions) in water, and hydrolyzed polymaleic anhydride can inhibit the growth of scale crystals, thus forming an efficient scale inhibition dual defense mechanism.
[0012] Secondly, after adding imidazoline oleyl polyamine corrosion inhibitor and 2-amino-5-methyl-4-phenylthiazole, they can form stable chemical bonds or intermolecular forces with the modified polyaspartic acid-hydrolyzed polymaleic anhydride protective film, strengthen the protective film structure, make it more dense and complete, greatly enhance the barrier ability to corrosive substances (such as sulfides, acidic substances, etc.), and provide more reliable corrosion protection for metal equipment in high temperature, high pressure and complex chemical petroleum processing environments. Moreover, the polar groups in its molecular structure can interact with the polar parts in organic scale, change the surface properties of organic scale, reduce the deposition tendency, and combine the repelling effect of the hydrophobic groups of modified polyaspartic acid on organic scale and the dispersing effect of hydrolyzed polymaleic anhydride on organic scale, to construct a more complete anti-organic scale deposition system, maintain the cleanliness of the equipment surface, and ensure the normal operation of the equipment, especially in preventing the heat transfer efficiency of heat exchange equipment from decreasing due to the accumulation of organic scale.
[0013] Finally, solution E was added first and then dispersion D. The dispersant in solution E created favorable conditions for the uniform dispersion of nano-titanium dioxide and nano-zinc oxide in the system, enabling them to closely combine with the protective film components and other corrosion and scale inhibition components formed previously, and effectively fill the tiny pores and defects in the protective film, making the protective film denser, thereby enhancing its barrier ability to corrosive substances (such as sulfides, acidic substances, etc.), and significantly improving the corrosion inhibition performance. At the same time, nano-titanium dioxide and nano-zinc oxide also have certain photocatalytic activity and antibacterial properties. In some cases, they can decompose organic pollutants and microorganisms that may be attached to the metal surface, reduce the possibility of biofilm formation, and further improve the comprehensive protective performance of the corrosion and scale inhibition system, effectively guaranteeing the long-term stable operation of metal equipment under complex working conditions, and reducing equipment failures and increased maintenance costs caused by corrosion, scaling and microbial growth.
[0014] Preferably, the preparation method of modified polyaspartic acid comprises the following steps: Under an inert atmosphere, at 60-80°C, aspartic acid is dissolved in ethanolamine, mixed evenly to obtain an aspartic acid solution, heated to 130-150°C, reacted for 1.5-2.5 hours, then dioctyl terephthalate is added, mixed evenly, heated to 150-170°C, reacted for 3-5 hours, modified silicon dioxide is added, mixed evenly, heated to 160-180°C, reacted for 4-6 hours, cooled to 80-100°C, a precipitant is added, solid-liquid separation is performed, washed, and dried to obtain modified polyaspartic acid; The amount of dioctyl terephthalate used is 20% to 30% of the mass of aspartic acid; the amount of modified silicon dioxide used is 5% to 10% of the total mass of aspartic acid and dioctyl terephthalate.
[0015] Preferably, in the aspartic acid solution, the mass fraction of aspartic acid is 30% to 40%.
[0016] Beneficial effects: First, due to the presence of dioctyl terephthalate and modified silica, the molecular structure of modified polyaspartic acid is more stable. The long hydrophobic chain of dioctyl terephthalate can be arranged in order on the metal surface to build a denser and more stable physical barrier layer, which greatly hinders the direct contact between corrosive substances such as sulfides and the surface of metal equipment. Therefore, it can still effectively protect metal equipment from erosion by sulfides in high temperature environment, so that its corrosion inhibition performance can be fully exerted.
[0017] Secondly, the hydrophobic group of dioctyl terephthalate gives modified polyaspartic acid excellent oleophobicity. When facing oily components such as gum and asphaltene commonly found in diesel, this oleophobic property exhibits a strong repulsive force, which can effectively prevent the adsorption and deposition of coke precursors (such as gum and asphaltene) on the surface of the equipment, thereby effectively reducing the formation of coke and maintaining the heat transfer efficiency of the equipment and normal material flow.
[0018] Finally, there is a certain synergistic effect between the chelation of modified polyaspartic acid and the adsorption function of modified silica. On the one hand, modified polyaspartic acid can chelate with scale-forming components (such as calcium carbonate, calcium sulfate, etc.) through its active groups, inhibiting the formation of scale from a chemical level; on the other hand, modified silica has a strong adsorption capacity for impurity ions in water due to its abundant surface active sites, further reducing the possibility of scale formation. In addition, for various types of salt impurities that may be mixed in the processing process, modified polyaspartic acid can also play its unique role. By chelating with metal ions, it prevents these salts from crystallizing and depositing, thereby effectively avoiding the risk of blockage of key equipment such as pipelines and heat exchangers, and ensuring the efficient and safe operation of the entire processing system.
[0019] Preferably, the method for preparing the modified silicon dioxide comprises the following steps: (1) Adding silica to an alkaline solution, mixing evenly, heating to 60-80°C, mixing for 2-4 hours, cooling, solid-liquid separation, washing, and drying to obtain hydroxylated silica; (2) Add hydroxylated silica to toluene, mix well to obtain a suspension, then add oleic acid, mix well, then add dibutyltin dilaurate, mix well, heat to 80-100°C, react for 3-6 hours, cool, separate solid from liquid, wash, and dry to obtain pre-modified silica; (3) Add the silane coupling agent to the ethanol aqueous solution, mix evenly, adjust the pH to 4-5, mix for 1-1.5 hours at room temperature to obtain a hydrolyzate; then add the pre-modified silica, mix evenly, heat to 50-70°C, react for 2-5 hours, separate the solid and liquid, wash, and dry to obtain modified silica; The amount of the oleic acid is 8% to 15% of the mass of the silicon dioxide, and the amount of the silane coupling agent is 5% to 10% of the mass of the silicon dioxide.
[0020] Preferably, the alkaline solution is a sodium hydroxide solution, the concentration of the sodium hydroxide solution is 0.5-1 mol / L, and the mass ratio of the silicon dioxide to the alkaline solution is 1:(10-20).
[0021] Preferably, the mass fraction of silicon dioxide in the suspension is 10% to 20%.
[0022] Preferably, the amount of dibutyltin dilaurate is 0.5% to 2% of the mass of oleic acid.
[0023] Preferably, in the ethanol-water solution, the volume ratio of ethanol to water is (4-9):1.
[0024] Preferably, the mass ratio of the silicon dioxide to the hydrolyzate is 1:(10-15).
[0025] Beneficial effects: Through the above modification steps, the structure of silica is optimized. The introduction of oleic acid and silane coupling agent covers the surface of silica with a layer of organic molecules. The long-chain hydrocarbon group of oleic acid has good hydrophobicity and flexibility, and can be entangled and interlaced with the molecular chain of polyaspartic acid, further enhancing the physical interaction between the two. The silane coupling agent plays a "bridge" role between silica and polyaspartic acid. The siloxane group at one end reacts with the hydroxyl group on the surface of silica, and the organic functional group at the other end can be chemically bonded with polyaspartic acid, thereby achieving a close connection between the modified silica and polyaspartic acid at the molecular level, so that the modified polyaspartic acid can be more firmly adsorbed on the metal surface in practical applications, improving the durability of its corrosion and scale inhibition performance. In addition, the coating of the organic molecular layer not only improves its compatibility and binding force with polyaspartic acid, but also provides silica with a certain thermal stability and chemical stability. In high-temperature environments (such as the high-temperature reaction area during diesel processing), the organic molecular layer can reduce the chemical reaction between silica and the surrounding medium, and its own thermal stability also helps to maintain the structural integrity of the entire modified polyaspartic acid.
[0026] Preferably, the modified polyaspartic acid further comprises the following pretreatment steps before use: S11: dispersing the modified polyaspartic acid in toluene and mixing them evenly to obtain a modified polyaspartic acid dispersion; S12: dissolving aluminum isopropoxide in anhydrous isopropanol at 70-80° C., mixing uniformly to obtain an aluminum isopropoxide solution, then adding deionized water to the aluminum isopropoxide, and adding acetic acid to adjust the pH to 4-5, reacting for 5-7 hours, and obtaining a transparent alumina sol; S13: slowly adding the modified polyaspartic acid dispersion to the alumina sol in step S12, mixing evenly, heating to 80-90° C., keeping the temperature for 4-6 hours, separating the solid from the liquid, washing, and drying to obtain; The mass ratio of the modified polyaspartic acid to aluminum isopropoxide is 1:(0.4-0.6).
[0027] Preferably, the mass ratio of the deionized water to aluminum isopropoxide is 1:4.
[0028] Preferably, in the modified polyaspartic acid dispersion, the mass fraction of modified polyaspartic acid is 10% to 15%; and in the aluminum isopropoxide solution, the mass fraction of aluminum isopropoxide is 15% to 20%.
[0029] Beneficial effects: On the one hand, the mechanical strength and stability of the protective film formed by the modified polyaspartic acid coated with alumina sol are significantly improved. Alumina builds a solid support skeleton with its stable chemical structure and physical properties. In the harsh environment of high temperature, high pressure and rich in highly corrosive media such as hydrogen sulfide and acidic substances in processing processes such as hydrocracking and catalytic diesel, the skeleton can effectively resist the impact of external stress and corrosion factors, effectively ensure the integrity of the protective film, and continuously and efficiently play its role in corrosion protection of metal equipment.
[0030] On the other hand, the high specific surface area and excellent adsorption performance brought by the alumina sol coating create favorable conditions for the adsorption and dispersion of scaling precursors. In working conditions prone to scaling problems such as coking diesel units, alumina can efficiently adsorb scaling precursors such as colloids, asphaltene and metal ions, preventing them from aggregating on the surface of the equipment and causing scaling reactions. At the same time, the anti-scaling properties of the modified polyaspartic acid itself further work synergistically, not only inhibiting the chemical reaction of the adsorbed substances into scaling, but also during the entire operation of the device, for the scaling that may be formed, the coating structure can significantly reduce its tendency to adhere to the surface of the equipment. The rough surface and chemical inertness of alumina make it difficult for scaling to adhere tightly, and the modified polyaspartic acid reduces the affinity between scaling and the surface from a chemical level. The two complement each other and effectively reduce the deposition of scaling on the equipment.
[0031] Preferably, the preparation method of the corrosion and scale inhibitor further comprises adding an additive accounting for 1.5% to 3.5% of the mass of the modified polyaspartic acid, and the step of adding the additive is: in step S3, a portion of the additive is added after 2-amino-5-methyl-4-phenylthiazole, and the mixture is mixed evenly to obtain a mixture C; In step S6, after adding dispersion D, mixing evenly, heating to 130-150°C, reacting for 3-5 hours, adding another part of additives, reacting for 40-60 minutes, cooling, solid-liquid separation, and distillation, a corrosion and scale inhibitor is obtained; the additives include polytetrafluoroethylene and polyetheretherketone.
[0032] Preferably, the additive undergoes the following pretreatment steps before use: S21: treating polytetrafluoroethylene and polyetheretherketone with plasma at a power of 100-200 W for a treatment time of 5-10 min to obtain a pretreatment additive; S22: dissolving dopamine hydrochloride in tris-hydrochloric acid buffer to prepare a dopamine solution with a dopamine concentration of 1-2 mg / ml; S23: adding the pretreatment additive to the dopamine solution, reacting at room temperature for 18 to 24 hours, separating the solid from the liquid, washing to neutrality, and drying to obtain the additive; The ratio of the total mass of the polytetrafluoroethylene and polyetheretherketone to the volume of the dopamine solution is 1g: (30-50)ml.
[0033] Preferably, the mass ratio of polytetrafluoroethylene to polyetheretherketone is (2-3):1.
[0034] Beneficial effects: The pretreated additives can form a more stable and efficient protective layer in the corrosion and scale inhibitor system. First, after the plasma treatment, the surface activity of both increases. After reacting with dopamine hydrochloride, they can be better dispersed in the corrosion and scale inhibitor system, and adsorbed and aggregated on the metal surface. It can not only effectively prevent corrosive substances (such as sulfides, acidic substances, etc.) from contacting the metal and reduce the occurrence of corrosion; it also helps to reduce the erosion and wear of the metal surface by the fluid, further protecting the metal equipment; it can also provide the necessary mechanical strength support for the protective layer, so that it can remain intact under complex working conditions (such as high temperature, high pressure, fluid impact, etc.), and is not easily damaged, so as to continue to play a role in corrosion inhibition and scale inhibition.
[0035] Secondly, the addition of pre-treated additives can also reduce the surface energy of the metal surface, making it difficult for scale (such as calcium carbonate, calcium sulfate, etc.) and organic scale (such as colloid, asphaltene) to deposit and adhere to the metal surface. Even if a small amount of scale is formed, the smooth surface of polytetrafluoroethylene makes it difficult for the scale to adhere firmly and is easy to fall off under the scouring of the fluid, thereby keeping the surface of the metal equipment clean, improving the heat transfer efficiency and operating stability of the equipment, and reducing equipment failures and maintenance costs caused by scaling.
[0036] Finally, there is a synergistic effect between the additive and other corrosion and scale inhibition components (such as modified polyaspartic acid, hydrolyzed polymaleic anhydride, imidazoline oleoyl polyamine corrosion inhibitors, etc.). Among them, the chelation effect of modified polyaspartic acid can capture scale-forming metal ions in water, and the additive can further inhibit the possibility of these captured ions forming scales. At the same time, the protective layer formed by the additive also provides a more stable environment for the adsorption and action of modified polyaspartic acid and other components on the metal surface, so that its corrosion and scale inhibition performance can be better exerted. This synergistic effect significantly improves the performance of the entire corrosion and scale inhibition system, which can adapt to more complex and harsh diesel processing environments and effectively protect metal equipment.
[0037] In summary, this application has the following beneficial effects: 1. This application uses chemical bonding between modified polyaspartic acid and hydrolyzed polymaleic anhydride and entanglement of molecular chains to enable the entire system to maintain structural integrity under high temperature environment, and the corrosion inhibition mechanisms of the two complement each other, inhibiting the occurrence of corrosion reactions from different angles such as chelating metal ions and adsorbing to change the surface properties of metals. At the same time, the addition of imidazoline oleoyl polyamine corrosion inhibitor, 2-amino-5-methyl-4-phenylthiazole and dispersion D further strengthens the structural integrity and stability of the protective film. They form stable chemical bonds or intermolecular forces with the formed protective film, greatly enhancing the ability to block corrosive substances, and providing reliable and long-term corrosion protection for equipment such as diesel processing under high temperature, high pressure and complex and changeable chemical substances.
[0038] 2. The chelation of modified polyaspartic acid can accurately capture scale-forming metal ions (such as calcium ions, magnesium ions, etc.) in water, preventing them from combining with anions to form scale crystal nuclei, while hydrolyzed polymaleic anhydride can effectively inhibit the growth of scale crystals, doubly blocking the formation path of scale (such as calcium carbonate, calcium sulfate and other common scale types) from the source and in the process, and constructing an efficient scale prevention mechanism. At the same time, the addition of imidazoline oleoyl polyamine corrosion inhibitor, 2-amino-5-methyl-4-phenylthiazole and dispersion D cooperates with the above-mentioned scale prevention mechanism to inhibit the formation and deposition of organic scale from multiple angles.
[0039] 3. The addition of additives further improves the anti-scaling performance. It can not only inhibit the adhesion and deposition of scale through its own chemical properties, but also synergize with other anti-scaling ingredients to enhance the anti-scaling effect.
[0040] 4. The dispersant in solution E plays a key stabilizing and dispersing role in the entire system, ensuring that all components are evenly dispersed in the hydrogenated diesel, preventing particle agglomeration and sedimentation, and enabling the corrosion and scale inhibitor to maintain stable physical and chemical properties under different temperatures, pressures and chemical environments, ensuring that the synergistic effect between the components can be continuously and effectively exerted. DETAILED DESCRIPTION
[0041] The present application is further described in detail below with reference to embodiments.
[0042] The corrosion and scale inhibitor prepared in the present application is mainly suitable for the early stages of processing processes such as hydrocracking, catalytic diesel and coking diesel, including raw oil pretreatment, preliminary treatment of reaction products, etc., to help reduce equipment corrosion and scaling.
[0043] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.
[0044] Hydrolyzed polymaleic anhydride, 99%, was purchased from Jingzhou Yinjie Chemical Co., Ltd.; Imidazoline oleoyl polyamine type corrosion inhibitor, the main component of which is oleoyl acetyl polyamine, was purchased from Lanzhou Fine Chemical High-tech Development Company; 2-Amino-5-methyl-4-phenylthiazole was purchased from (Alpha) Henan Weitixi Chemical Technology Co., Ltd.; Polyaspartic acid was purchased from Shandong DeLan Chemical Co., Ltd.; The particle size distribution of silicon dioxide is 10-15 μm; the particle size distribution of nano zinc oxide and nano titanium oxide is 1-100 nm; the particle size distribution of polytetrafluoroethylene and polyetheretherketone is 5-15 μm; before use, the above particles are placed in a drying oven, dried at 80°C to constant weight, and slightly ground and dispersed.
[0045] Preparation Examples 1~3 Modified Silica Preparation Example 1 (1) Slowly add 100 g of silica to 1000 g of 1 mol / L sodium hydroxide solution, stirring at 500 rpm. After the addition is completed, continue stirring for 20 min, then heat to 60 ° C, continue stirring and react for 4 h, cool to room temperature, centrifuge, wash with deionized water until neutral, transfer to a vacuum drying oven, and dry at 80 ° C to constant weight to obtain hydroxylated silica; (2) Slowly add hydroxylated silica to 900 g of toluene while stirring at a speed of 600 rpm. After the addition is completed, continue stirring for 30 minutes, then add 8 g of oleic acid, continue stirring for 40 minutes, then add 0.16 g of dibutyltin dilaurate, continue stirring for 15 minutes, turn on the heating device, raise the temperature to 80°C, react for 6 hours, cool to room temperature, centrifuge, wash three times with a mixed solvent of toluene and ethanol (the volume ratio of toluene to ethanol is 2:1), transfer to a vacuum drying oven, and dry to constant weight at 80°C to obtain pre-modified silica; (3) Add 5 g of γ-aminopropyltriethoxysilane to 495 g of ethanol aqueous solution, stir and mix evenly, use 10% by mass acetic acid to adjust the pH to between 4 and 5, stir for 1 h at room temperature, rotate at 300 rpm, then add pre-modified silica, adjust the rotation speed to 500 rpm, mix for 120 min, heat to 50 ° C, react for 5 h, cool to room temperature, centrifuge, wash alternately with ethanol and deionized water twice each, transfer to a vacuum drying oven, and dry at 80 ° C to constant weight to obtain modified silica.
[0046] Among them, in the ethanol-water solution, the volume ratio of ethanol to water is 4:1.
[0047] Preparation Example 2 (1) Slowly add 100 g of silica to 2000 g of 0.5 mol / L sodium hydroxide solution, stirring at 500 rpm. After the addition is completed, continue stirring for 20 min, then heat to 80 ° C, continue stirring and react for 2 h, cool to room temperature, centrifuge, wash with deionized water until neutral, transfer to a vacuum drying oven, and dry at 80 ° C to constant weight to obtain hydroxylated silica; (2) Slowly add hydroxylated silica to 400 g of toluene while stirring at a speed of 600 rpm. After the addition is completed, continue stirring for 60 min, then add 15 g of oleic acid, continue stirring for 40 min, then add 0.075 g of dibutyltin dilaurate, continue stirring for 15 min, turn on the heating device, raise the temperature to 100 ° C, react for 3 h, cool to room temperature, centrifuge, wash three times with a mixed solvent of toluene and ethanol (the volume ratio of toluene to ethanol is 2:1), transfer to a vacuum drying oven, and dry to constant weight at 80 ° C to obtain pre-modified silica; (3) Add 10 g of γ-aminopropyltriethoxysilane to 490 g of ethanol aqueous solution, stir and mix evenly, use 10% by mass acetic acid to adjust the pH to between 4 and 5, stir for 2.5 h at room temperature, rotate at 300 rpm, then add pre-modified silica, adjust the speed to 500 rpm, mix for 120 min, heat to 70 ° C, react for 2 h, cool to room temperature, centrifuge, wash alternately with ethanol and deionized water twice each, transfer to a vacuum drying oven, and dry at 80 ° C to constant weight to obtain modified silica.
[0048] Among them, the volume ratio of ethanol to water in the ethanol aqueous solution is 9:1.
[0049] Preparation Example 3 (1) Slowly add 100 g of silica to 1000 g of 1 mol / L sodium hydroxide solution, stirring at 500 rpm. After the addition is completed, continue stirring for 20 min, then heat to 70 ° C, continue stirring and react for 3 h, cool to room temperature, centrifuge, wash with deionized water until neutral, transfer to a vacuum drying oven, and dry at 80 ° C to constant weight to obtain hydroxylated silica; (2) Slowly add hydroxylated silica to 600 g of toluene while stirring at a speed of 600 rpm. After the addition is completed, continue stirring for 40 min, then add 12 g of oleic acid, continue stirring for 40 min, then add 0.12 g of dibutyltin dilaurate, continue stirring for 15 min, turn on the heating device, raise the temperature to 90 ° C, react for 5 h, cool to room temperature, centrifuge, wash three times with a mixed solvent of toluene and ethanol (the volume ratio of toluene to ethanol is 2:1), transfer to a vacuum drying oven, and dry to constant weight at 80 ° C to obtain pre-modified silica; (3) Add 8 g of γ-aminopropyltriethoxysilane to 492 g of ethanol aqueous solution, stir and mix evenly, use 10% by mass acetic acid to adjust the pH to between 4 and 5, stir for 2 h at room temperature, rotate at 300 rpm, then add pre-modified silica, adjust the rotation speed to 500 rpm, mix for 120 min, heat to 60 ° C, react for 3 h, cool to room temperature, centrifuge, wash alternately with ethanol and deionized water twice each, transfer to a vacuum drying oven, and dry at 80 ° C to constant weight to obtain modified silica.
[0050] Among them, the volume ratio of ethanol to water in the ethanol aqueous solution is 5:1.
[0051] Preparation Examples 4-6 Modified Polyaspartic Acid Preparation Example 4 Under nitrogen atmosphere, at 60°C, 400g of aspartic acid ground through a 80-mesh sieve was added to 933g of ethanolamine, stirred and mixed for 60min, heated to 130°C, reacted for 2.5h, and then 80g of dioctyl terephthalate was slowly added dropwise for 40min. After the addition was completed, the temperature was raised to 150°C and reacted for 5h. Then 24g of modified silica was added, stirred and mixed for 30min, heated to 160°C, reacted for 6h, cooled to 80°C, and 5% calcium chloride solution was added dropwise until no precipitate was precipitated. The mixture was vacuum filtered, washed with anhydrous ethanol 3 times, transferred to a vacuum drying oven, and dried at 80°C for 6h to obtain modified polyaspartic acid.
[0052] The modified silica is from Preparation Example 1.
[0053] Preparation Example 5 Under nitrogen atmosphere, at 80°C, 400g of aspartic acid ground through a 80-mesh sieve was added to 600g of ethanolamine, stirred and mixed for 60min, heated to 150°C, reacted for 1.5h, and then 120g of dioctyl terephthalate was slowly added dropwise for 60min. After the addition was completed, the temperature was raised to 170°C and reacted for 3h. Then 52g of modified silica was added, stirred and mixed for 60min, heated to 180°C, reacted for 4h, cooled to 100°C, and a 5% calcium chloride solution was added dropwise until no precipitate was precipitated. The mixture was vacuum filtered, washed with anhydrous ethanol 3 times, transferred to a vacuum drying oven, and dried at 80°C for 6h to obtain modified polyaspartic acid.
[0054] Among them, the modified silica comes from Preparation Example 2.
[0055] Preparation Example 6 Under nitrogen atmosphere, at 70°C, 400g of aspartic acid ground through an 80-mesh sieve was added to 800g of ethanolamine, stirred and mixed for 60min, heated to 140°C, reacted for 2h, and then 100g of dioctyl terephthalate was slowly added dropwise for 50min. After the addition was completed, the temperature was raised to 160°C and reacted for 4h. Then 40g of modified silica was added, stirred and mixed for 60min, heated to 170°C, reacted for 5h, cooled to 90°C, and 5% calcium chloride solution was added dropwise until no precipitate was precipitated. The mixture was vacuum filtered, washed with anhydrous ethanol 3 times, transferred to a vacuum drying oven, and dried at 80°C for 6h to obtain modified polyaspartic acid.
[0056] Among them, the modified silica comes from Preparation Example 3.
[0057] Preparation Example 7 S11: adding 400 g of modified polyaspartic acid into 3600 g of toluene, stirring and mixing for 30 min at a speed of 300 rpm to obtain a dispersion with a mass fraction of 10%; S12: After adding 907g of isopropanol to a three-necked flask, place it in a constant temperature water bath at 70°C, turn on the stirring device at a speed of 300rpm, then slowly add 160g of aluminum isopropoxide, stir and mix until the aluminum isopropoxide is fully dissolved to obtain a solution with a mass fraction of 15%, then use a constant pressure dropping funnel to dropwise add 40g of deionized water (conductivity not higher than 1μS / cm) to the above solution, control the dropping speed at 10-20 drops per minute, add acetic acid at the same time, adjust the pH to between 4 and 5, react for 7h, and obtain a transparent alumina sol; S13: Slowly add the dispersion to the alumina sol in step S12, and adjust the stirring speed to 500 rpm. After the addition is completed, heat to 80°C and continue stirring for 6 hours. After the reaction is completed, transfer the reaction system to a rotary evaporator, and remove isopropanol and toluene solvent by reduced pressure distillation at a vacuum degree of 0.09 MPa and a temperature of 80°C to obtain a solid product. Wash the solid product three times with an equal volume of n-hexane, transfer it to a vacuum drying oven, and dry it at 70°C for 12 hours.
[0058] Among them, the modified polyaspartic acid comes from Preparation Example 6.
[0059] Preparation Example 8 S11: adding 400 g of modified polyaspartic acid into 2267 g of toluene, stirring and mixing for 30 min at a speed of 300 rpm to obtain a dispersion with a mass fraction of 15%; S12: After adding 960g of isopropanol to a three-necked flask, place it in a constant temperature water bath at 80°C, turn on the stirring device at a speed of 300rpm, then slowly add 240g of aluminum isopropoxide, stir and mix until the aluminum isopropoxide is fully dissolved to obtain a solution with a mass fraction of 20%, then use a constant pressure dropping funnel to dropwise add 60g of deionized water (conductivity not higher than 1μS / cm) to the above solution, control the dropping speed at 10-20 drops per minute, add acetic acid at the same time, adjust the pH to between 4 and 5, react for 5h, and obtain a transparent alumina sol; S13: Slowly add the dispersion dropwise to the alumina sol in step S12, and adjust the stirring speed to 500 rpm. After the addition is completed, raise the temperature to 90°C and continue stirring the reaction for 4 hours. After the reaction is completed, transfer the reaction system to a rotary evaporator, and remove the isopropanol and toluene solvent by reduced pressure distillation at a vacuum degree of 0.09 MPa and a temperature of 80°C to obtain a solid product. Wash the solid product three times with an equal volume of n-hexane, transfer it to a vacuum drying oven, and dry it at 70°C for 16 hours.
[0060] Among them, the modified polyaspartic acid comes from Preparation Example 6.
[0061] Example 1 This embodiment provides a method for preparing a corrosion and scale inhibitor, comprising the following steps: S1: At 50°C, 250 g of modified polyaspartic acid was slowly added to 750 g of hydrogenated diesel, and the mixture was stirred at 300 rpm for 30 min until it was uniform. Then, 1.25 g of antioxidant 1010 was added, and the mixture was stirred and mixed for 20 min to obtain a solution A with a mass fraction of 25% of modified polyaspartic acid. S2: 150 g of hydrolyzed polymaleic anhydride was added to 850 g of hydrogenated diesel, and the mixture was stirred at 300 rpm for 40 min until it became uniform, to obtain a solution B having a mass fraction of hydrolyzed polymaleic anhydride of 15%; S3: 60 g of imidazoline oleyl polyamine corrosion inhibitor and 10 g of 2-amino-5-methyl-4-phenylthiazole were placed in a stirring device at a rotation speed of 300 rpm, and stirred for 30 minutes until they were uniform, to obtain a mixture C; S4: First, 4 g of sodium dodecylbenzene sulfonate was added to 456 g of hydrogenated diesel, and stirred at 300 rpm for 25 min, and then 20 g of nano titanium dioxide and 20 g of nano zinc oxide were added respectively, and the mixture was stirred and mixed for 40 min until it was uniform, to obtain a dispersion D with a total mass fraction of nano titanium dioxide and nano zinc oxide of 8%; S5: adding 40 g of polyisobutylene succinimide to 960 g of hydrogenated diesel, stirring at 40° C. and 300 rpm for 50 min to obtain a solution E having a polyisobutylene succinimide mass fraction of 4%; S6: Under nitrogen atmosphere, solution A and solution B were added to the reactor, stirred and mixed at a speed of 200 rpm for 15 minutes, heated to 110°C, reacted for 2.5 hours, and then mixture C was added, stirred and mixed at a speed of 300 rpm for 20 minutes until uniform, heated to 150°C, reacted for 6 hours, cooled to 90°C, solution E was added, stirred and mixed at a speed of 400 rpm for 60 minutes, and then dispersion D was added, and stirring and mixing was continued for 120 minutes. The temperature was raised to 130°C, reacted for 5 hours, and then cooled. The product was filtered through a filter with an aperture of 100 mesh to remove residual large particle impurities, and then the filtrate was transferred to a vacuum distillation device, and rotary evaporated at 80°C and 0.07~0.09MPa for 3 hours to obtain a slow-release scale inhibitor.
[0062] Among them, the modified polyaspartic acid comes from Preparation Example 4.
[0063] Example 2 This embodiment provides a method for preparing a corrosion and scale inhibitor, comprising the following steps: S1: At 70°C, 350 g of modified polyaspartic acid was slowly added to 650 g of hydrogenated diesel, and the mixture was stirred at 300 rpm for 30 min until it was uniform. Then, 3.5 g of antioxidant 1010 was added, and the mixture was stirred and mixed for 20 min to obtain a solution A with a mass fraction of 35% of modified polyaspartic acid. S2: 250 g of hydrolyzed polymaleic anhydride was added to 750 g of hydrogenated diesel, and the mixture was stirred at 300 rpm for 40 min until it became uniform, to obtain a solution B having a mass fraction of hydrolyzed polymaleic anhydride of 25%; S3: 100 g of imidazoline oleyl polyamine corrosion inhibitor and 20 g of 2-amino-5-methyl-4-phenylthiazole were placed in a stirring device at a rotation speed of 300 rpm, and stirred for 30 minutes until a uniform state was obtained to obtain a mixture C; S4: First, 7 g of sodium dodecylbenzene sulfonate was added to 506 g of hydrogenated diesel, and the mixture was stirred at 300 rpm for 25 min. Then, 42 g of nano titanium dioxide and 28 g of nano zinc oxide were added respectively, and the mixture was stirred and mixed for 40 min until a uniform state was obtained to obtain a dispersion D having a total mass fraction of nano titanium dioxide and nano zinc oxide of 12%; S5: adding 80 g of polyisobutylene succinimide to 920 g of hydrogenated diesel, stirring at 60° C. and 300 rpm for 50 min to obtain a solution E having a mass fraction of polyisobutylene succinimide of 8%; S6: Under nitrogen atmosphere, solution A and solution B were added to the reactor, stirred and mixed at a speed of 200 rpm for 15 minutes, heated to 130°C, reacted for 1.5 hours, and then mixture C was added, stirred and mixed at a speed of 300 rpm for 20 minutes until uniform, heated to 170°C, reacted for 4 hours, cooled to 110°C, solution E was added, stirred and mixed at a speed of 400 rpm for 60 minutes, and then dispersion D was added, and stirring and mixing was continued for 120 minutes. The temperature was raised to 150°C, reacted for 4 hours, cooled, and the product was filtered through a filter with an aperture of 100 mesh to remove residual large particle impurities. The filtrate was then transferred to a vacuum distillation device, and rotary evaporated at 80°C and 0.07~0.09MPa for 2 hours to obtain a slow-release scale inhibitor.
[0064] Among them, the modified polyaspartic acid comes from Preparation Example 5.
[0065] Example 3 This embodiment provides a method for preparing a corrosion and scale inhibitor, comprising the following steps: S1: At 60°C, 300 g of modified polyaspartic acid was slowly added to 700 g of hydrogenated diesel, and the mixture was stirred at 300 rpm for 30 min until it was uniform. Then, 3 g of antioxidant 1010 was added, and the mixture was stirred and mixed for 20 min to obtain a solution A with a mass fraction of modified polyaspartic acid of 30%; S2: 200 g of hydrolyzed polymaleic anhydride was added to 800 g of hydrogenated diesel, and the mixture was stirred at 300 rpm for 40 min until the mixture became uniform, to obtain a solution B having a mass fraction of hydrolyzed polymaleic anhydride of 20%; S3: 80 g of imidazoline oleyl polyamine corrosion inhibitor and 15 g of 2-amino-5-methyl-4-phenylthiazole were placed in a stirring device at a rotation speed of 300 rpm, and stirred for 30 minutes until they were uniform, to obtain a mixture C; S4: First, 6 g of sodium dodecylbenzene sulfonate was added to 534 g of hydrogenated diesel, and the mixture was stirred at 300 rpm for 25 min. Then, 40 g of nano titanium dioxide and 20 g of nano zinc oxide were added respectively, and the mixture was stirred and mixed for 40 min until a uniform state was obtained to obtain a dispersion D having a total mass fraction of nano titanium dioxide and nano zinc oxide of 10%; S5: adding 60 g of polyisobutylene succinimide to 940 g of hydrogenated diesel, stirring at 50° C. and 300 rpm for 50 min to obtain a solution E having a polyisobutylene succinimide mass fraction of 6%; S6: Under nitrogen atmosphere, solution A and solution B were added to the reactor, stirred and mixed at a speed of 200 rpm for 15 minutes, heated to 120°C, reacted for 2 hours, and then mixture C was added, stirred and mixed at a speed of 300 rpm for 20 minutes until uniform, heated to 160°C, reacted for 5 hours, cooled to 100°C, solution E was added, stirred and mixed at a speed of 400 rpm for 60 minutes, and then dispersion D was added, and stirring and mixing was continued for 120 minutes. The temperature was raised to 140°C, reacted for 3 hours, and then cooled. The product was filtered through a filter with an aperture of 100 mesh to remove residual large particle impurities, and then the filtrate was transferred to a vacuum distillation device, and rotary evaporated at 80°C and 0.07~0.09MPa for 2.5 hours to obtain a slow-release scale inhibitor.
[0066] Among them, the modified polyaspartic acid comes from Preparation Example 6.
[0067] Example 4 The difference between this embodiment and embodiment 3 is that: The modified polyaspartic acid is from Preparation Example 7.
[0068] The rest is the same as in Example 3.
[0069] Example 5 The difference between this embodiment and embodiment 3 is that: The modified polyaspartic acid is from Preparation Example 8.
[0070] The rest is the same as in Example 3.
[0071] Example 6 The difference between this embodiment and embodiment 5 is that: S3: 80 g of imidazoline oleyl polyamine corrosion inhibitor, 15 g of 2-amino-5-methyl-4-phenylthiazole and 2.25 g of additive were placed in a stirring device at a rotation speed of 300 rpm, and stirred for 30 minutes until a uniform state was obtained to obtain a mixture C; S6: Under nitrogen atmosphere, solution A and solution B were added to the reactor, stirred and mixed at a speed of 200 rpm for 15 minutes, heated to 120°C, reacted for 2 hours, and then mixture C was added, stirred and mixed at a speed of 300 rpm for 20 minutes until uniform, heated to 160°C, reacted for 5 hours, cooled to 100°C, solution E was added, stirred and mixed at a speed of 400 rpm for 60 minutes, and then dispersion D was added, and stirring and mixing was continued for 120 minutes. The temperature was raised to 140°C, reacted for 3 hours, and 2.25 g of additive was added. The reaction was stirred for 40 minutes, cooled, and the product was filtered through a filter with an aperture of 100 mesh to remove residual large particle impurities. The filtrate was then transferred to a vacuum distillation device, and rotary evaporated for 2.5 hours at 80°C and 0.07~0.09MPa to obtain a slow-release scale inhibitor.
[0072] Among them, the additives undergo the following pretreatment steps before use: S21: 3 g of polytetrafluoroethylene and 1.5 g of polyetheretherketone are subjected to plasma treatment at a power of 100 W for a treatment time of 10 min to obtain a pretreatment additive; S22: dissolving 270 mg of dopamine hydrochloride in 135 ml of tris(hydroxymethylaminomethane)-hydrochloric acid buffer (pH 8.5) to prepare a dopamine solution having a dopamine concentration of 2 mg / ml; S23: adding the pretreatment additive to the dopamine solution, reacting at room temperature for 18 hours, separating the solid and the liquid, washing with deionized water until neutral, transferring to a vacuum drying oven at 60° C. and drying to constant weight to obtain the additive.
[0073] The rest is the same as Example 5.
[0074] Example 7 The difference between this embodiment and embodiment 6 is that: In step S3, the amount of the additive used is 5.25 g; in step S6, the amount of the additive used is 5.25 g.
[0075] Among them, the additives undergo the following pretreatment steps before use: S21: 7.9 g of polytetrafluoroethylene and 2.6 g of polyetheretherketone are subjected to plasma treatment at a power of 200 W for a treatment time of 5 min to obtain a pretreatment additive; S22: dissolving 525 mg of dopamine hydrochloride in 525 ml of tris(hydroxymethylaminomethane)-hydrochloric acid buffer (pH 8.5) to prepare a dopamine solution having a dopamine concentration of 1 mg / ml; S23: adding the pretreatment additive to the dopamine solution, reacting at room temperature for 24 hours, separating the solid and the liquid, washing with deionized water until neutral, transferring to a vacuum drying oven at 60° C. and drying to constant weight to obtain the additive.
[0076] The rest is the same as Example 6.
[0077] Comparative Example 1 The difference between this comparative example and Example 1 is: Polyaspartic acid was unmodified and obtained from a commercial source.
[0078] The rest is the same as in Example 1.
[0079] Performance Testing The test raw material used in this performance test is hydrocracking crude oil.
[0080] 1. Corrosion rate determination (1) Hanging method The corrosion and scale inhibitors prepared in Examples 1-7 and Comparative Example 1 were tested according to GB / T18175-2014 standard. Nine reactors were taken and marked as test pieces 1 to 9 in sequence. 1.5L of hydrocracking crude oil was added respectively. The first 8 reactors were added with the slow-release scale inhibitors in Examples 1 to 7 and Comparative Example 1 in sequence. The addition concentration was 100ppm. The last reactor was used as a blank control group. Three carbon steel sheets and three stainless steel sheets were placed in each reactor. The temperature was raised to 200°C and kept warm for 72 hours. After the temperature was reached, the reactor was cooled, washed, dried and weighed. After the average value of each group was obtained, the corrosion rate of test pieces 1 to 8 was calculated in combination with the blank control group. The test results are shown in Table 1. Among them, the carbon steel sheet and the stainless steel sheet were pre-cleaned, dried and weighed, and the initial mass was recorded to an accuracy of 0.1 mg.
[0081] (2) Dynamic corrosion performance measurement The corrosion and scale inhibitors prepared in Examples 1-7 and Comparative Example 1 were tested according to the HG-T2160-2008 standard. Nine reactors were taken and marked as samples 1 to 9 in sequence. 1.5L of hydrocracking crude oil was added respectively. The first 8 reactors were added with the slow-release scale inhibitors in Examples 1 to 7 and Comparative Example 1 in sequence. The addition concentration was 100ppm. The last reactor was used as a blank control group. Three carbon steel test tube samples were placed in each reactor. The temperature was raised to 200°C and kept warm for 7 days. After the temperature was reached, the samples were cooled, washed, dried and weighed. After the average value of each group was obtained, the corrosion rate of samples 1 to 8 was calculated in combination with the blank control group. The test results are shown in Table 2. Among them, the carbon steel test tube samples were cleaned in advance, dried and weighed, and the initial mass was recorded to an accuracy of 0.1 mg.
[0082] 2. Determination of scale inhibition rate The corrosion and scale inhibitors prepared in Examples 1-7 and Comparative Example 1 were tested according to HG / T2024-2009, and 9 measuring tubes were selected. The first 8 used hydrocracking raw oil mixed with corrosion and scale inhibitors to be fed into different measuring tubes at a flow rate of 120 g / h, and the last one was used as a blank control group. The hydrocracking raw oil was fed into the measuring tube at a flow rate of 120 g / h. All measuring tubes were heated by a heater, and the temperature was maintained at 200°C. After 24 hours of such a cycle, the measuring tubes were cooled to room temperature, the raw oil was discharged, washed, dried and weighed, and the amount of scale accumulation was measured. According to the different amounts of scale accumulation in the blank control group and the experimental group using the corrosion and scale inhibitors in Examples 1 to 7 and Comparative Example 1, the scale inhibition rate was obtained, and the test results are shown in Table 3. Among them, the test tubes were pre-cleaned, dried and weighed, and the initial mass was recorded to an accuracy of 0.1 mg.
[0083] Table 1 Corrosion rate performance test results of test pieces 1 to 8
[0084] Table 2 Dynamic corrosion rate test results of samples 1 to 8
[0085] Table 3 Test results of scale inhibition rate of corrosion and scale inhibitors prepared in Examples 1 to 7 and Comparative Example 1
[0086] Analyzing the test results in Table 1 to Table 3, we can see that: It can be seen from Example 1 and Comparative Example 1 that the modification of polyaspartic acid brings about a significant performance improvement in the field of hydrocracking feedstock oil. This is because a stable composite system is formed through the synergistic effect between polyaspartic acid, dioctyl benzoate and silica, which not only enhances the dispersibility of polyaspartic acid in the feedstock oil, but also improves its slow-release scale inhibition performance.
[0087] It can be seen from Examples 1 to 3 that by optimizing and adjusting the distribution ratio of each group, the corrosion and scale inhibitors all exhibit good corrosion and scale inhibition performance.
[0088] It can be seen from Examples 3 to 5 that by pretreating the modified polyaspartic acid, a layer of alumina sol will be coated on the surface of the modified polyaspartic acid. This composite structure can be better adsorbed on the metal surface. At the same time, alumina can also serve as a physical barrier to prevent the corrosive medium from contacting the metal, thereby improving the corrosion inhibition performance.
[0089] The dispersion performance of the modified polyaspartic acid after pretreatment is improved, which helps it to be evenly distributed in the crude oil, and can better interact with the scale-forming ions to prevent them from crystallizing and forming scale. At the same time, the combination of alumina sol and modified polyaspartic acid will produce a certain synergistic effect. Alumina sol will adsorb some scale-forming ions, and modified polyaspartic acid can prevent these ions from further aggregating and growing, thereby improving the scale inhibition rate.
[0090] It can be seen from Examples 5 to 7 that by introducing additives, they can synergize with modified polyaspartic acid and other ingredients to form a denser protective film, while enhancing the adsorption and scale ion dispersion capabilities of the corrosion and scale inhibitor system, and preventing the aggregation and crystallization of scale ions to a greater extent.
Claims
1. A method for preparing a corrosion and scale inhibitor, characterized in that: The steps include: S1: dissolving 25-35 parts by mass of modified polyaspartic acid in hydrogenated diesel, adding an antioxidant, and mixing well to obtain solution A; S2: dissolving 15-25 parts by mass of hydrolyzed polymaleic anhydride in hydrogenated diesel and mixing well to obtain solution B; S3: 6-10 parts by weight of imidazoline oleyl polyamine corrosion inhibitor and 1-2 parts by weight of 2-amino-5-methyl-4-phenylthiazole are uniformly mixed to obtain a mixture C; S4: adding 0.4-0.7 parts by mass of sodium dodecylbenzene sulfonate to hydrogenated diesel, mixing evenly, and then adding nano titanium dioxide and nano zinc oxide in a mass ratio of 1-2:1, mixing evenly, to obtain a dispersion D; S5: dissolving 4 to 8 parts by weight of the dispersant in hydrogenated diesel and mixing them uniformly to obtain a solution E; S6: Under an inert atmosphere, solution A and solution B are mixed in a reactor, mixed evenly, heated to react, then mixture C is added, mixed evenly, heated to react, cooled, solution E is added, mixed evenly, then dispersion D is added, mixed evenly, heated to react, cooled, solid-liquid separation is performed, and distillation is performed to obtain a corrosion and scale inhibitor; The total amount of the nano titanium dioxide and nano zinc oxide is 4 to 7 parts by weight.
2. The method for preparing the corrosion and scale inhibitor according to claim 1, characterized in that: In step S6, under an inert atmosphere, solution A and solution B are mixed in a reactor, mixed evenly, heated to 110-130°C, reacted for 1.5-2.5 hours, and then mixture C is added, mixed evenly, heated to 150-170°C, reacted for 4-6 hours, cooled to 90-110°C, solution E is added, mixed evenly, and then dispersion D is added, mixed evenly, heated to 130-150°C, reacted for 3-5 hours, cooled, solid-liquid separation, and distilled to obtain a corrosion inhibitor and scale inhibitor.
3. The method for preparing the corrosion and scale inhibitor according to claim 1, characterized in that: The dispersant is polyisobutylene succinimide.
4. The method for preparing the corrosion and scale inhibitor according to claim 1, characterized in that: The antioxidant is antioxidant 1010, and the amount of the antioxidant 1010 is 0.5% to 1% of the mass of the modified polyaspartic acid.
5. The method for preparing the corrosion and scale inhibitor according to claim 1, characterized in that: The preparation method of the modified polyaspartic acid comprises the following steps: Under an inert atmosphere, at 60-80°C, aspartic acid is dissolved in ethanolamine, mixed evenly to obtain an aspartic acid solution, heated to 130-150°C, reacted for 1.5-2.5 hours, then dioctyl terephthalate is added, mixed evenly, heated to 150-170°C, reacted for 3-5 hours, modified silicon dioxide is added, mixed evenly, heated to 160-180°C, reacted for 4-6 hours, cooled to 80-100°C, a precipitant is added, solid-liquid separation is performed, washed, and dried to obtain modified polyaspartic acid; The amount of dioctyl terephthalate used is 20% to 30% of the mass of aspartic acid; the amount of modified silicon dioxide used is 5% to 10% of the total mass of aspartic acid and dioctyl terephthalate.
6. The method for preparing the corrosion and scale inhibitor according to claim 5, characterized in that: The preparation method of the modified silicon dioxide comprises the following steps: (1) Adding silica to an alkaline solution, mixing evenly, heating to 60-80°C, mixing for 2-4 hours, cooling, solid-liquid separation, washing, and drying to obtain hydroxylated silica; (2) Add hydroxylated silica to toluene, mix well to obtain a suspension, then add oleic acid, mix well, then add dibutyltin dilaurate, mix well, heat to 80-100°C, react for 3-6 hours, cool, separate solid from liquid, wash, and dry to obtain pre-modified silica; (3) Add the silane coupling agent to the ethanol aqueous solution, mix evenly, adjust the pH to 4-5, mix for 1-1.5 hours at room temperature to obtain a hydrolyzate; then add the pre-modified silica, mix evenly, heat to 50-70°C, react for 2-5 hours, separate the solid and liquid, wash, and dry to obtain modified silica; The amount of the oleic acid is 8% to 15% of the mass of the silicon dioxide, and the amount of the silane coupling agent is 5% to 10% of the mass of the silicon dioxide.
7. The method for preparing the corrosion and scale inhibitor according to claim 5, characterized in that: Before the modified polyaspartic acid is used, the following pretreatment steps are also included: S11: dispersing the modified polyaspartic acid in toluene and mixing them evenly to obtain a modified polyaspartic acid dispersion; S12: dissolving aluminum isopropoxide in anhydrous isopropanol at 70-80° C., mixing uniformly to obtain an aluminum isopropoxide solution, then adding deionized water to the aluminum isopropoxide, and adding acetic acid to adjust the pH to 4-5, reacting for 5-7 hours, and obtaining a transparent alumina sol; S13: slowly adding the modified polyaspartic acid dispersion to the alumina sol in step S12, mixing evenly, heating to 80-90° C., keeping the temperature for 4-6 hours, separating the solid from the liquid, washing, and drying to obtain; The mass ratio of the modified polyaspartic acid to aluminum isopropoxide is 1:(0.4-0.6).
8. The method for preparing the corrosion and scale inhibitor according to claim 1, characterized in that: The preparation method of the corrosion and scale inhibitor further includes adding an additive accounting for 1.5% to 3.5% of the mass of the modified polyaspartic acid, wherein the step of adding the additive is as follows: in step S3, a portion of the additive is added after 2-amino-5-methyl-4-phenylthiazole, and the mixture is mixed evenly to obtain a mixture C; In step S6, after adding dispersion D, mixing evenly, heating to 130-150°C, reacting for 3-5 hours, adding another part of additives, reacting for 40-60 minutes, cooling, solid-liquid separation, and distillation, a corrosion and scale inhibitor is obtained; the additives include polytetrafluoroethylene and polyetheretherketone.
9. The method for preparing the corrosion and scale inhibitor according to claim 8, characterized in that: Before the additive is used, it undergoes the following pretreatment steps: S21: treating polytetrafluoroethylene and polyetheretherketone with plasma at a power of 100-200 W for a treatment time of 5-10 min to obtain a pretreatment additive; S22: dissolving dopamine hydrochloride in tris-hydrochloric acid buffer to prepare a dopamine solution with a dopamine concentration of 1-2 mg / ml; S23: adding the pretreatment additive to the dopamine solution, reacting at room temperature for 18 to 24 hours, separating the solid from the liquid, washing to neutrality, and drying to obtain the additive; The ratio of the total mass of the polytetrafluoroethylene and polyetheretherketone to the volume of the dopamine solution is 1g: (30-50)ml.
10. The method for preparing the corrosion and scale inhibitor according to claim 8, characterized in that: The mass ratio of the polytetrafluoroethylene to polyetheretherketone is (2-3):1.
Citation Information
Patent Citations
Preparation and application of scale inhibitor in oil refining process
CN114591760A
Diesel oil improver component containing biological enzyme and preparation method and application thereof
CN103421554A
Low-sulfur diesel oil additive composition, and preparation method and application of same
CN103450955A
Low-temperature non-solidification phosphorus-free corrosion and scale inhibitor and preparation method and scale inhibition method thereof
CN113716710A
Corrosion inhibitor for cooling water system of marine diesel engine as well as preparation method and application of corrosion inhibitor
CN118908432A
Cited By
Self-breathing anti-scaling cathode, preparation method, electrolytic bath and application of self-breathing anti-scaling cathode
CN121023552A